Malaysian pop music in the minority language : A tool for forging unity and a common identity. - Collin, Jerome; Esther John, Perry; Ting, Su Hie (ACADEMIA INDUSTRY NETWORKS, 2022)
Numerous studies have demonstrated that modern popular songs in the majority language can forge a sense of national identity, unity, and pride among the masses. However, popular songs written and sung in the minority language have the same ability and even more. The present study examined this disparity by gathering the views and opinions of the Malaysian masses through self-administered surveys regarding Lagu pop Iban (Iban pop song) and its connection to identity and unity. The findings showed that the respondents, most of whom originated from the Malaysian state of Sarawak, possessed a good knowledge of Iban pop songs, displayed positive attitudes towards them and engaged with this music genre in varied ways. The findings also showed there was an agreement among the respondents regarding Iban pop songs' ability to foster a commonsense of belonging and a shared identity over time, despite their different views on this matter. One of the implications of these findings is that the role of music in minority languages should be accepted and recognized as a tool for forging unity and a common identity within the context of multiracial, multilingual, and multicultural nation-states.